Pandangan Kongres Ulama Perempuan Indonesia terhadap Kekerasan Berbasis Gender Online di Media Sosial Twitter - Zalikho Su'ada; Neng Hannah (Az-Zahra: Journal of Gender and Family Studies, 2023)
The phenomenon of violence against women in the online world is not only facilitated but has shifted to exist with the help of digital technology. Online Gender-Based Violence (KBGO) is prone to attack women, considering that patriarchal patterns and power relations are the main problems. One form Act of Gender-Based Violence (KBGO) that enlivens the social media universe on Twitter is the banning of illicit fatwas by Saudi Arabian clerics on the use of Breast Holders (BH) or Bras in front of other men who are not their mahram, which had become a hot topic and was disseminated massively on social media Twitter. This research uses qualitative methods through interview techniques accompanied by several supporting sources such as documentation and literature studies. This study aims to bring other alternatives to the Islamic perspective that are able to change, make the perpetrator's perspective aware, and increase public awareness of the real form of KBGO. KUPI (Congress of Indonesian Women Ulama) Indonesia is a network of female ulama in Indonesia, which initiated a religious interpretation movement that protects women's groups, to view and respond critically to the existence of fatwas and discourses of expectations for the use of Breast Holders (BH) or Bras in front of other men who are not their mahram. The results of this study include first, Online-Based Gender Violence (KBGO) occurs because of power relations against women, where there is a hierarchical, unequal relationship and dependence on social status and culture, as well as the knowledge that gives rise to more than one party's power over the other. Others secondly, KUPI strongly rejects the phenomenon of online-based gender violence (KBGO) and argues that the fatwa prohibiting the use of bras for women in front of men who are not their mahrams and widely distributed on Twitter is included in the category of online-based gender violence. (KBGO), as well as KUPI discourse, any religious fatwa must be viewed and treated critically and constructively, especially the fatwa concerning and discussing women's fundamental rights in various fields of life, whether religious, political, social, or cultural.